2016
DOI: 10.1186/s41100-016-0035-1
|View full text |Cite
|
Sign up to set email alerts
|

Inguinal hernia in hemodialysis versus peritoneal dialysis patients: a case-control study

Abstract: Background: Inguinal hernia is common in dialysis patients, especially peritoneal dialysis (PD) patients; however, no previous reports have assessed the incidence, type, treatments, and risk factors of inguinal hernia in hemodialysis (HD) patients. We retrospectively evaluated the differences in these factors between HD and PD patients. Methods: A total of 2287 HD and 410 PD patients treated between March 2006 and December 2013 were enrolled. The incidence, type (indirect, direct, or combined), and hernioplast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
2
4
0
Order By: Relevance
“…The current study showed that male gender and PD were the risk factors for inguinal hernia development in patients with ESRD. Furthermore, the current findings are comparable with previous reports [8,14] although others observed no complications. [12,15] Abdominal wall hernia, especially inguinal hernia, which accounts for 83.08% of all hernia in the present study, is a common mechanical PD complication.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The current study showed that male gender and PD were the risk factors for inguinal hernia development in patients with ESRD. Furthermore, the current findings are comparable with previous reports [8,14] although others observed no complications. [12,15] Abdominal wall hernia, especially inguinal hernia, which accounts for 83.08% of all hernia in the present study, is a common mechanical PD complication.…”
Section: Discussionsupporting
confidence: 93%
“…The current study showed that male gender and PD were the risk factors for inguinal hernia development in patients with ESRD. Furthermore, the current findings are comparable with previous reports [8,14] although others observed no complications. [12,15]…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations